Pengaruh Pengalaman Kerja Terhadap Kinerja Karyawan di Bandungan Koffie di Bandungan Kabupaten Semarang - Dyah Purwaningrum; Galih Panjalu Pramono (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
Work experience is believed to improve employees' abilities and skills in completing assigned tasks. Through literature studies and primary data collection, this study is expected to provide empirical contributions regarding the relationship between work experience and employee performance. The results of this study are expected to be a reference for companies in formulating policies related to employee career development and improving organizational performance. Performance is the result of work achieved by a person or group in a certain period. This work result can be measured and assessed based on established standards or criteria. Performance is often associated with effectiveness and efficiency in achieving established goals. This study examines the effect of work experience on employee performance by considering the moderating role of work motivation. The hypothesis of this study is that work experience has a positive effect on employee performance, and this effect is stronger when employee performance is high. The Effect of Employee Work Experience on Employee Performance at Bandungan Koffe in Semarang Regency. With good employee performance, it is expected to trigger work enthusiasm towards the Company's vision and mission. The research method used is quantitative research using a simple linear regression method. The sample in this study amounted to 50 respondents using the census method. Data collection using questionnaires and data processing using the SPSS realis 2.2 analysis tool.  Based on the results of this study, it is shown that from the results of a simple linear regression analysis with the help of the SPSP relase 2.2 program, a simple linear regression test obtained the regression equation:  Y = 12.485 + 0.353 X so it can be concluded that work experience has a positive effect on employee performance